KINDS OF TRANSLATION METHOD USED BY THE STUDENT'S IN TRANSLATING DESCRIPTIVE TEXT FROM ENGLISH TO INDONESIAN - Susi Rosalina Sipahutar; Elen Magdalena Marpaung; Ester Riska Sianturi; Kartina Rahmadhani Rambe (Universitas Putera Batam, 2021)
This research aimed to analyze the kinds of translation method used by the eight grade students at SMP Yayasan Perguruan Karya Bhakti. The method of this research was descriptive qualitative. The sample of this research was the eight grade students at SMP Yayasan Karya Bhakti. There are two instruments of this research, namely the first test is about translating the English text into Bahasa and the second test is interview test, there are 10 questions in interview test. In translation analysis process, the researchers used theory of translation method based on Newmark theory. The findings of this research showed that there are only four method used by the students in translating the text. They are Literal Translation, Faithful Translation, Word-for-Word Translation and Free Translation. It can be seen from the table that the most dominat method used by 10 students was literal translation and faithful translation method. The second dominant was word-for-word translation and free translation method. Here, the students used more than one method to tranlate the descriptive text.